Jones, Robert (audio interview #1 of 1) - Jones, Robert; Andriesse, Ann, interviewer
INTERVIEW DESCRIPTION - This single, one hour interview was conducted in Jones office adjacent to the Midway Fishing Tool warehouse. He was patient in explaining the origin of fishing tools and talking about the many ways they can be made and used to an interview who had little technical knowledge. 11/4/1981